2017
DOI: 10.4103/0974-8237.199878
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of “idiopathic” syrinx by atlantoaxial fixation: Report of an experience with nine cases

Abstract: Objective:The authors evaluate the significance of atlantoaxial instability in the management of idiopathic syringomyelia.Background:We recently observed that atlantoaxial dislocation can be present even when the atlantodental interval was within normal range. Atlantoaxial instability can be identified on the basis of facetal mal-alignment or even by direct observation of status of joint during surgery. Our observations are discussed in nine patients where we identified and treated atlantoaxial instability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Identification of central instability as a nodal point of the pathogenesis of a number of clinical entities can have a defining impact on their surgical management. [ 4 5 6 7 8 ] We identified that following atlantoaxial fixation, apart from recovery from neurological symptoms, there can be the reversal of secondary musculoskeletal changes and neural alterations such as short neck, torticollis, basilar invagination, Chiari formation, and syringomyelia. [ 5 6 7 8 9 ] In addition, the patient had C3-4 fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of central instability as a nodal point of the pathogenesis of a number of clinical entities can have a defining impact on their surgical management. [ 4 5 6 7 8 ] We identified that following atlantoaxial fixation, apart from recovery from neurological symptoms, there can be the reversal of secondary musculoskeletal changes and neural alterations such as short neck, torticollis, basilar invagination, Chiari formation, and syringomyelia. [ 5 6 7 8 9 ] In addition, the patient had C3-4 fusion.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently identified that atlantoaxial fixation can be the treatment for “idiopathic” syringomyelia and for syringomyelia associated with Chiari formation. [ 5 7 8 ] It was reported that following atlantoaxial fixation, the clinical symptoms recovered dramatically, and the syringomyelia cavity regressed in size in a significant number of cases. [ 5 7 8 ] Our current observation is that when the follow-up imaging is done after more than a year, the syringomyelia cavity regressed in 100 percent cases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 14 ] Our further evaluations of craniovertebral junction-related issues conclude that atlantoaxial instability is the basis of a number of musculoskeletal abnormalities, such as basilar invagination, bone fusions or Klippel-Feil abnormality, assimilation of atlas, C2-3 fusion, bifid posterior arch of atlas, platybasia, short neck, and torticollis, as well as neural abnormalities, such as Chiari formation and syringomyelia, when they are present in conjunction or in isolation. [ 33 34 35 36 37 ] The observation has significant clinical relevance and suggests the need for atlantoaxial fixation in all the mentioned clinical entities and futility of foramen magnum decompression surgery as the mode of surgical treatment. As we identified decrease in the size of syrinx and reversal of tonsillar herniation, we identified reversal of musculoskeletal changes of basilar invagination that begins in the immediate postoperative period following atlantoaxial fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic or longstanding atlantoaxial instability is associated with a host of ‘secondary’ musculoskeletal and neural ‘alterations.’ Musculoskeletal alterations include a number of morphological changes that include platybasia, Klippel-Feil abnormality, assimilation of atlas, bifid arch of atlas and C2–3 fusion and neural alterations that include Chiari formation and syringomyelia [ 13 - 15 ]. The term ‘basilar invagination’ in general is an umbrella term that includes a range of alterations.…”
mentioning
confidence: 99%